Isolasi Dan Karakterisasi Bakteri Simbion Larva Kupu-Kupu Cossus cossus Penghasil Enzim Selulase - Maswati Baharuddin; Abd. Rauf Patong; Ahyar Ahmad; Nursiah La Nafie (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2014)
This study was conducted to characterize bacterial symbionts of butterfly larvae Cossus cossus capable of degrading cellulose. This study successfully purify and characterize isolates originating from the intestine (CC1 and CC2), head (CC3), middle (CC4), and tail (CC5). From a qualitative test using 0.1% congo red gained the clear zone indicates that the bacteria are able to degrade cellulose. Based on the test temperature and pH on the growth of the data obtained CC5 isolates including isolates of thermophilic bacteria, while others including mesophilic bacteria. While based pH test all isolates were able to grow well at neutral pH. Based on the data obtained growth curve maximum bacterial growth at the 24th hour. Based on morphology and physiology test obtained bacteria genus Acinotobacter, Pseudomonas, and Bacillus.